Enhancing oxygen/moisture resistance of quantum dots by short-chain, densely cross-linked silica glass network. (12th November 2022) - Yang, Xuan; Zhou, Shuling; Zhang, Xinfeng; Xiang, Linyi; Xie, Bin; Luo, Xiaobing
Abstract: Quantum dots (QDs) are facing significant photoluminescence degradation in moisture environment. In QDs-silicone composites, the poor water resistance of silicone matrix makes it easy for water and oxygen molecules to erode QDs. To tackle this issue, we proposed a new QDs protection strategy by introducing short-chain silica precursors onto the QDs' surface, so that a dense silica passivation layer could be formed onto the QDs nanoparticles. Sol-gel method based on 3-aminopropyl triethoxysilane (APTES), 3-mercaptopropyl trimethoxysilane (MPTMS), and 3-mercaptopropyl triethoxysilane (MPTES) were adopted to prepare the uniform and crack-free QDs-silica glass (QD-glass). Because of the crosslinking of short-chain precursors, the formed silica glass possesses 38.6% smaller pore width and 68.6% lower pore volume than silicone, indicating its denser cross-linked network surrounding QDs. After 360 h water immersion, the QDs-glass demonstrated a 6% enhancement in red-light peak intensity, and maintained a stable full width at half maximum (FWHM) and peak wavelength, proving its excellent water-resistant ability. However, the conventional QDs-silicone composites not only showed a decrease of 75.3% in red-light peak intensity, but also a broadened FWHM and a redshifted peak wavelength after water immersion. QDs-glass also showed superior photostability after 132 h exposure to blue light. Red-light peak intensity of QDs-glass remained 87.3% of the initial while that of QDs-silicone decreased to 19.8%. And the intensity of QDs-glass dropped to 62.3% of that under 20 °C after thermal treatment of 160 °C. Besides, under increasing driving currents, the light conversion efficiency drop of QDs-glass is only one fifth that of QDs-silicone. Based on the QDs-glass, the white light-emitting diodes was achieved with a high luminous efficiency of 126.5 lm W −1 and a high color rendering index of 95.4. Thus, the newly proposed QD-glass has great significance in guaranteeing the working reliability of QDs-converted devices against moisture and high-power environment.